Case Report: A rare form of congenital erythrocytosis due to SLC30A10 biallelic variants—differential diagnosis and recommendation for biochemical and genetic screening - Giannini, Rosalinda; Agolini, Emanuele; Palumbo, Giuseppe; Novelli, Antonio; Garone, Giacomo; Grasso, Melissa; Colafati, Giovanna Stefania; Matraxia, Marta; Piccirilli, Eleonora; Deodati, Annalisa; Ceglie, Giulia (Frontiers in Pediatrics, 2024)
Congenital erythrocytosis recognizes heterogeneous genetic basis and despite the use of NGS technologies, more than 50% of cases are still classified as idiopathic. Herein, we describe the case of a 3-year-old boy with a rare metabolic disorder due to SLC30A10 bi-allelic mutations and characterized by hypermanganesemia, congenital erythrocytosis and neurodegeneration, also known as hypermanganesemia with dystonia 1 (HMNDYT1). The patient was treated with iron supplementation and chelation therapy with CaNa2EDTA, resulting in a significative reduction of blood manganese levels and erythrocytosis indexes. Although it couldn't be excluded that the patient's developmental impairment was part of the phenotypic spectrum of the disease, after three months from starting treatment no characteristic extrapyramidal sign was detectable. Our findings suggest the importance of assessing serum manganese levels in patients with unexplained polycythemia and increased liver enzymes. Moreover, we highlight the importance of extended genetic testing as a powerful diagnostic tool to uncover rare genetic forms of congenital erythrocytosis. In the described patient, identifying the molecular cause of erythrocytosis has proven essential for proper clinical management and access to therapeutic options.